(untitled) (Sciences & Technologie. B, Sciences de l’ingénieur, 2003)
A practical quasi-three dimensional inverse computation model is developed for the design of turbopump under the assumption of inviscid incompressible flow. The three-dimensional flow through impellers is decomposed into a circumferentially averaged mean flow and a periodic flow according to flow periodicity. In this computation the blade geometry of impeller is designed according to specified blade bound circulation distribution and normal thickness distribution on a given meridional geometry. In the first step, we use the meridional stream function to define the flow field. The governing equation is deduced from the relation between the azimuthal component of the vorticity and the meridional velocity. In the second step, the inverse problem corresponding to the blade to blade flow confined in each stream sheet is analyzed. The blade geometry is determined according to a specified blade bound circulation distribution by iterative computation of S2 and S1 surfaces.